Healthcare providers’ knowledge on sickle cell disease and its management: A pre- and post-training test evaluation outcome - Vivian Paintsil; Evans Xorse Amuzu; Eunice Ahmed; Yaa Gyamfua Oppong-Mensah; Lesley Osei; Bernice Eklu; Suraj Yawnumah Abubakar; Lawrence Osei-Tutu; Daniel Ansong; Alex Osei-Akoto; Fred Stephen Sarfo (PLoS ONE, 2025)
In resource-limited settings in Africa, which harbour the greatest burden of Sickle Cell Disease (SCD) globally, poor care outcomes are driven in part, by a lack of trained healthcare providers (HCP) and an absence of context-specific treatment guidelines appropriate to the level of healthcare facility. The study aimed to evaluate the impact of a structured training program on HCP’s knowledge of SCD in Ghana. This was prospective cross-sectional study involving HCPs from 46 health facilities from 4 out of 16 regions in Ghana. A curriculum and standard slides were developed by SCD experts based on the Sickle Pan African Research Consortium (SPARCO)Standards of care for Sickle Cell Disease in sub-Saharan Africa clinical recommendations. A full-day workshop highlighting the general overview of SCD, diagnosis, health maintenance, acute and chronic complications was then organized. A pre-training test and a post-training test immediately after the workshop were administered and analyzed. A total of 543 HCPs were trained, mostly from primary level facilities (77.7%). The average number of years working with SCD patients was 5 years (Range: < 1–20 years). Most (93%) HCPs had experience with SCD patients but only 43% reported using a form of guideline for the care of SCD patients. The average score in the pre-training test was 8.4/20 (SD:3.3) increasing to 13.1/20(SD:3.6) in the post-training test, (p-value <0.01). The average proportion of persons indicating a correct answer for a question was 50% at the pre-training test increasing to approximately 69% in the post-test, (p-value <0.01). The knowledge of HCPs about SCD and its management was generally low but improved significantly after the standardized training. Further studies are required to assess the impact of HCP training on health outcomes of SCD in resource limited settings.